-x-42=-3x+14

Simple and best practice solution for -x-42=-3x+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-42=-3x+14 equation:


Simplifying
-1x + -42 = -3x + 14

Reorder the terms:
-42 + -1x = -3x + 14

Reorder the terms:
-42 + -1x = 14 + -3x

Solving
-42 + -1x = 14 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-42 + -1x + 3x = 14 + -3x + 3x

Combine like terms: -1x + 3x = 2x
-42 + 2x = 14 + -3x + 3x

Combine like terms: -3x + 3x = 0
-42 + 2x = 14 + 0
-42 + 2x = 14

Add '42' to each side of the equation.
-42 + 42 + 2x = 14 + 42

Combine like terms: -42 + 42 = 0
0 + 2x = 14 + 42
2x = 14 + 42

Combine like terms: 14 + 42 = 56
2x = 56

Divide each side by '2'.
x = 28

Simplifying
x = 28

See similar equations:

| 5(-x+7)=20 | | 10-5(9n-9)=10-5 | | 6y-2=-3 | | 20y^2+9y-20=0 | | 04(1.5c+6)-2c=-9 | | x-20=60 | | 3x+6y+4z=2900 | | 7x-11=3x-3 | | 140=192-w | | -3x+6(2x+9)=9 | | 5x-34=17 | | x+10=400 | | 2x+3x+15=30 | | 3+2n= | | 125=-w+236 | | -2r+6(r-1)+3r-(4-r)=(r+5)-5 | | 4-7j=f-12 | | 1+1=8 | | -v+61=185 | | (7t-2)(-3t+1)=-3(1-3t) | | 22-6=4h | | 85+17x=-87+13x | | 11x-6=6x+14 | | 5(x+2)=3k-1 | | x+x+2+x+4+x+6=464 | | -5.9-(-4.9)= | | x+x+1+x+2=156 | | 102=9x | | -136+2x=6x+132 | | y=20+3x | | 9=3v+37+4v | | y=0.15x+2.94 |

Equations solver categories